Cover Feature: Primary Amine Catalyzed Activation of Carbonyl Compounds: A Study on Reaction Pathways and Reactive Intermediates by Mass Spectrometry (Eur. J. Org. Chem. 3/2022). Issue 3 (14th January 2022) - Iazzetti, Antonia; Mazzoccanti, Giulia; Bencivenni, Giorgio; Righi, Paolo; Calcaterra, Andrea; Villani, Claudio; Ciogli, Alessia
Abstract : The Cover Feature illustrates the screening of amino organocatalysts employed in the activation of carbonyl compounds by ESI‐MS. The off‐line reaction monitoring provided information on the active intermediates, the putative catalytic cycles, and the reaction speed. The ESI‐MS investigations coupled with the enantioselective HPLC data allow selecting the more efficient organocatalyst. Cover design by Alessia Ciogli and Simone Manetto. More information can be found in the Research Article by A. Ciogli et al .